2013
DOI: 10.21273/hortsci.48.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Nitrogen Sufficiency Ranges in Leaf Petiole Sap of Brassica oleracea L., Pac Choi Grown with Organic and Conventional Fertilizers

Abstract: Greenhouse experiments were conducted to determine the response of Brassica oleracea L., pac choi to fertilizer rates and sources and to establish optimal soluble nitrogen (N) application rates and nitrate meter sufficiency ranges. Conventional soluble fertilizer was formulated from inorganic salts with a 4:1 NO3-N:NH4-N ratio. Phosphorus (P) was held at 1.72 mm and potassium (K) at 0.83 mm for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…In lettuce crops, maximum values of 225-267 mg L -1 were recorded. These values are higher than the optimum found in some brassicas (150 mg L -1 ) (Altamimi et al, 2013). The wide variability observed in nitrate concentrations in this study may be due to imprecise applications of nitrogen fertilizers or, to their excessive amounts, which frequently incur in high lixiviation.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…In lettuce crops, maximum values of 225-267 mg L -1 were recorded. These values are higher than the optimum found in some brassicas (150 mg L -1 ) (Altamimi et al, 2013). The wide variability observed in nitrate concentrations in this study may be due to imprecise applications of nitrogen fertilizers or, to their excessive amounts, which frequently incur in high lixiviation.…”
Section: Resultscontrasting
confidence: 65%
“…Castellanos et al (1999) reported values between 600 to 900 mg L -1 in vertisol-type clay loam soils in the central region of Guanajuato, Mexico; high yields of broccoli are achieved in this place. Altamimi et al (2013) observed optimal yields at levels of 13 to 123 mg L -1 . The low content of K in SS recorded in some crops may be due to the low retention of this element by the soil.…”
Section: Resultsmentioning
confidence: 88%
“…To maintain uniform growing medium moisture across the blocks, an additional pac choi pot was placed at the corner of each bench, which served as an indicator container to determine when watering was needed. Pac choi plants received 750 mL of deionized water when the gravimetric weight of the indicator pots decreased by 30% from container capacity (Altimimi, 2010;Gardner, 1965) in adjacent blocks. Temperature and relative humidity were recorded using a HOBO data logger (Onset Computer Corp., Pocasset, MA) set at 30-min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The eight plants within each block were randomly assigned to receive either an organic or conventional fertilizer treatment (four organic and four conventional). The organic fertilizer was a soluble fish hydrolysate (Neptune's Harvest, Gloucester, MA) labeled as a 2.2N-4.3P-0.3K fertilizer and diluted to obtain a target concentration of 167 ppm N. This N concentration was selected based on previous greenhouse experiments associated with optimal N rates and pac choi yield (Altimimi, 2010). Three 100-mL diluted hydrolysate samples were submitted for nutrient testing [total N, total phosphorus (P) by potassium (K) persulfate digest, NO 3 --N, and NH 4 + -N in filtered samples by colorimetric analysis and P, K, Mg, sulfur (S), iron (Fe), sodium, and chlorine (Cl) in filtered samples analyzed by inductively coupled plasma spectroscopy] by the Soil Testing Laboratory at Kansas State University (Manhattan, KS).…”
Section: Methodsmentioning
confidence: 99%
“…Petiole sections were placed into a plant press (Zyliss, Farnborough, United Kingdom), manually pressed for approximately 10 s using consistent pressure, and approximately 20 drops of sap were collected into a 5 ml beaker. The sap was not diluted and followed approaches outlined in previous studies (Folegatti et al, 2005;Altamimi et al, 2013;Carson et al, 2016). Extracted sap was analyzed for NO 3 − , K + , and Ca 2+ concentrations using compact ion meters with ion selective electrode sensors (Horiba LAQUAtwin; Spectrum Technologies, Aurora, IL, United States).…”
Section: Plant Petiole Sap and Leaf Tissue Nutrient Analysismentioning
confidence: 99%